PEMANFAATAN TUMBUHAN KETAK SEBAGAI KERAJINAN TANGAN KHAS LOMBOK - Dwika Mazraatus Sakina; Nining Purwanti (Universitas Lambung Mangkurat, 2026)
Lombok Island is one of the islands that is famous for its agricultural island, besides being famous for its agricultural island, it is also famous for its objects and cultural customs. Lombok itself is a center for crafts. This study aims to preserve Indonesia's cultural heritage by understanding and developing ketak weaving crafts which are part of Lombok culture and increasing community income through the development of the ketak woven craft industry. This study uses a qualitative approach that is descriptive in nature, namely by conducting direct observation to understand how the process of making woven handicrafts from ketak plants by the Lombok community. The results of this study conclude that the role of ketak plants as handicraft materials has a strong cultural value in the Lombok area and can make it easier for people to find a livelihood and develop the ketak woven craft industry